Joint Game Algorithm of Power Control and Channel Allocation Considering Channel Interval and Relay Transmission Obstacle for WSN - Hao, Xiao-Chen; Ru, Xiao-Yue; Li, Xi-Da; Xin, Min-Jie (Wireless personal communications, 2016)
In order to effectively reduce network interference and decrease extra energy consumption, a joint power control and multi-channel game model is established in Wireless sensor network. The game model considers the interactions between power control and channel allocation. It has been proved the existence of Nash equilibrium. Based on this game model, a joint game algorithm of power control and channel allocation considering channel interval and relay transmission obstacle (JACIRT) is proposed. The theoretical analysis demonstrates that JACIRT can converge to the Pareto Optimal. The simulation results show that JACIRT can easily construct a topology which is connected and greatly reduces the interference. Besides, it decreases the channel interval, reduces the time of extra channel switching and energy consumption.